Prevalence and predictive factors associated with stunting in preschool children in a governorate of Iraq: a community-based cross-sectional study - Mhamad, Huda J.; Najmadden, Zana B.; Hama Salih, Kaihan H.; Hama, Dlkhwaz A.; Abdullah, Hiwa O.; Hasan, Karzan M.; Kareem, Honar O.; Mohammed, Bilal A.; Fattah, Fattah H.; Abdalla, Berun A.; Kakamad, Fahmi H.; Mohammed, Shvan H. (Frontiers in Nutrition, 2024)
Introduction The prevalence and risk factors of stunting in various geographical regions have been well investigated. However, not enough data exists regarding the communities in Iraq. This study investigated the prevalence and risk factors of stunting in preschool children in Halabja governorate. Methods The required data for the study was collected through a structured questionnaire form from the children’s parents. Then, the height and weight of the children were measured. According to the World Health Organization Child Growth Standards and using the WHO Anthro Survey Analyser software, children were classified as “stunted” when their height-for-age z-score was below two standard deviations. Results A total of 646 children were included, of which 310 (48%) were male and 336 (52%) were female. The gestational age of 556 (86%) children was 9 months, while 84 (13%) were born between 7–9 months, and 6 (1%) were born in 7 months. Regarding feeding during the first 2 years of life, 229 children (35.4%) were exclusively breastfed, 93 (14.4%) were bottle-fed, and 324 (50.2%) had mixed feeding. The prevalence of stunting was 7.9% in the sample pool, with 4.6% of females and 3.3% of males. Among stunted children, 6.35% were term babies, and 1.55% were preterm babies. None of the studied factors had a significant association with stunting. Conclusion The prevalence of stunting in the studied population was 7.9%. However, we could not find any significant association between the studied factors and stunting. Thus, the factors that may significantly affect stunting in our area of study, especially the historical chemical warfare side effects, need to be more extensively investigated in future studies.